Supraclavicular Block in Neglected Closed Fracture of the Intercondylar Humerus - Imunu, Naim Ismail; Siswagama, Taufiq Agus (Faculty of Medicine, Brawijaya University, 2025)
Background: The supraclavicular block is used in upper extremity surgery, offering the advantages of easy access, reliability, and low risk, with the added benefit of ultrasound guidance to enhance safety and effectiveness. The aim of this case study was to evaluate the effectiveness and role of the supraclavicular block with ultrasound as the primary anesthetic and analgesic technique in the surgical management of neglected closed intercondylar humeral fractures. Case: A 57-year-old woman presented with an intra-articular fracture of the distal third of the left humerus according to the osteosynthesefragen and the orthopedic trauma association (AO/OTA) classification, type C2, with soft tissue swelling on the dorsal aspect of the left elbow. The patient had diabetes and hypertension, American Society of Anesthesiologists (ASA) III, and a BMI of 27.8 kg/m2. The patient received a supraclavicular block with 0.5% ropivacaine and 10 mg dexamethasone in a total volume of 20 cm3. Needle placement was performed using ultrasound. During surgery, the patient received dexmedetomidine 0.3 µg/kg/hour plus intermittent fentanyl. Postoperatively, the patient was given ketorolac 3 x 30 mg and paracetamol 500 mg orally three times a day. One day after the procedure, the patient's numerical rating scale at rest was approximately 0 to 1, and a score of 1-2 was recorded during movement. Conclusion: A supraclavicular block, ultrasound-guided, with ropivacaine 0.5% can improve the accuracy and effectiveness of local anesthetic administration. This technique is helpful for patients with excess body mass because the brachial plexus is located superficially in the supraclavicular region